2021
DOI: 10.1186/s40510-021-00357-5
|View full text |Cite
|
Sign up to set email alerts
|

Stress distribution and displacement of three different types of micro-implant assisted rapid maxillary expansion (MARME): a three-dimensional finite element study

Abstract: Background/objective Until 2010, adults underwent surgical treatment for maxillary expansion; however, with the advent of micro-implant-assisted rapid maxillary expansion (MARME), the availability of less invasive treatment options has increased. Nevertheless, individuals with severe transverse maxillary deficiency do not benefit from this therapy. This has aroused interest in creating a new device that allows the benefit of maxillary expansion for these individuals. The aim of this study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…This study utilized FEA to primarily investigate and compare stress distribution patterns on the maxillary bone structure with different anteroposterior miniscrew positions of palatal slope bone-borne expander. Several studies 3,4,6,9,17,21 have shown that FEA is a beneficial method for analyzing stress, strain, and force distributions pertinent to orthodontic treatment of maxillary transverse discrepancy. Moreover, FEA is also an alternative, noninvasive, and convenient tool to study how maxillary bone and teeth respond to transverse force from maxillary expander.…”
Section: Discussionmentioning
confidence: 99%
“…This study utilized FEA to primarily investigate and compare stress distribution patterns on the maxillary bone structure with different anteroposterior miniscrew positions of palatal slope bone-borne expander. Several studies 3,4,6,9,17,21 have shown that FEA is a beneficial method for analyzing stress, strain, and force distributions pertinent to orthodontic treatment of maxillary transverse discrepancy. Moreover, FEA is also an alternative, noninvasive, and convenient tool to study how maxillary bone and teeth respond to transverse force from maxillary expander.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that maxillary disjunction generates strains and stresses in the cranial structures, especially in the zygomatic arch (29), as it represents a buttress of great resistance against maxillary expansion with high tension exerted in the orbit of the unpaired sphenoid bone, orbital ssure, and the pterygoid processes (30). Headache and diplopia due to increasing intracranial pressure (pseudotumor cerebri syndrome) have been reported (31).…”
Section: Formularendementioning
confidence: 99%
“…Formularbeginn Formularende But, according to Boryor's study (33), the upper rim of the zygomatic bone is also subjected to higher compressive stress, where the zygomaticomaxillary and zygomaticotemporal sutures act as mechanically elastic cranial components. Exceeding their elastic limits, especially in mature adult skulls that are less resilient, leads to a decrease in mechanical absorption, and therefore the occurrence of negative consequences (33,34).…”
Section: Formularendementioning
confidence: 99%
“…The effective opening of the midpalatal suture is an important basis for evaluating the effectiveness of the expander. The existing research methods on the opening of the midpalatal suture due to the excitation of the expander mainly include finite element analysis [ 20 , 21 , 22 , 23 ] and CT imaging [ 10 , 17 ]. The finite element method struggles to reproduce the fine structure of the complex jaw structure, the zygomaticomaxillary complex (ZMC), and the palatal expander structure, and CT imaging is complicated and difficult to monitor the complete process of palatal suture opening dynamically in real-time.…”
Section: Introductionmentioning
confidence: 99%